2022
DOI: 10.1007/s11695-021-05879-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Single-Anastomosis Duodeno-ileal Bypass with Sleeve Gastrectomy (SADI-S)

Abstract: Background Single-anastomosis duodeno-ileal bypass with sleeve gastrectomy (SADI-S) is a simplification of the duodenal switch (DS) in which the alimentary limb is eliminated, and the common channel is lengthened from 200 to 300 cm. Short-term results have demonstrated that SADI-S is safe and reproducible and that weight loss and comorbidities resolution are comparable to biliopancreatic diversion or DS. Objective To analyze the long-term outcomes of SADI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 37 publications
1
26
1
Order By: Relevance
“…SADI-S has been demonstrated to be a safe and reproducible technique and offers good weight loss results in the short term (66,67). Results on diabetes are comparable to those obtained with the duodenal switch (68), and some studies have even found a better metabolic effect thanks to the longer common channel (69,70).…”
Section: Single Anastomosis Duodenoileal Bypass With Sleeve Gastrecto...mentioning
confidence: 91%
See 1 more Smart Citation
“…SADI-S has been demonstrated to be a safe and reproducible technique and offers good weight loss results in the short term (66,67). Results on diabetes are comparable to those obtained with the duodenal switch (68), and some studies have even found a better metabolic effect thanks to the longer common channel (69,70).…”
Section: Single Anastomosis Duodenoileal Bypass With Sleeve Gastrecto...mentioning
confidence: 91%
“…Mean HbA1c was 5.51% at 5 years and 5.86% at 10 years. This allows concluding that in the long term, SADI-S seems to offer satisfactory weight loss and comorbidities resolution but there is insufficient data to comment on the long-term safety and efficacy of SADI-S (70). However, more studies should be done.…”
Section: Single Anastomosis Duodenoileal Bypass With Sleeve Gastrecto...mentioning
confidence: 99%
“…Surve et al, in their long-term outcome article, reported an average BMI of 30.1 kg/m 2 at 48 months [ 2 ]. Sánchez-Pernaute et al reported an average BMI of 27.5 kg/m 2 ; however, a majority of patients in their cohort received a 250-cm (60%) or 200-cm (30%) common channel [ 6 ]. Only 9% of the cohort received a 300-cm common channel.…”
Section: Discussionmentioning
confidence: 99%
“…Following surgery, patients were categorized into seven groups (3,6,12,18,24,36, and 48 months), based on months elapsed since surgery. The pre-surgery cohort readings for nutritional markers were grouped and labelled as group 0 to compare with group 3 (3 months), group 6 (6 months), group 12 (12 months), group 18 (18 months), group 24 (24 months), group 36 (36 months), and group 48 (48 months).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Finno et al 22 hypothesized that this reduction in the common channel is the primary cause of other micronutrient deficiencies, such as calcium, iron, copper, zinc, and folic acid. Thus, Sanchez-Pernaute et al 45 have proposed that patients must strictly adhere to 3 rules to counterbalance this high rate of nutritional deficiencies which are as follows: follow-up, dietary compliance, and supplementation. Furthermore, they recommended the consumption of at least 100 g of proteins and no more than 30% of fat per day for those who underwent the duodenal switch.…”
Section: Discussionmentioning
confidence: 99%